Molar - Incisor Hypomineralization (MIH) and long - term exposure to 25 - hydroxyvitamin D, measured as Bone Mineral Density (BMD) in adolescents from Northern Norway: an epidemiological study based on the Tromsø study: “Fit Futures” - Dekkerhus, Kristin Adelaide (UiT Norges arktiske universitet, 2020)
Aims: The basis of the study was to evaluate if MIH could be related to low levels of vitamin D. Vitamin D is understood to have a key role in both enamel and dentin formation, and maturation, in addition to skeletal integrity. BMD could give a clue of the participants’ long - term vitamin D exposure, indirectly giving a reflection of a possible vitamin D impact on enamel mineralization. Materials and Methods: Data from a cross-sectional health survey among adolescents from Northern Norway in 2010 - 2011, called Fit Futures were used in the present study. All participants born in 1994 with data available from the MIH-study was selected. Only participants with completed blood tests and BMD measurements among these were included in the analyzes. The statistical difference between MIH affected and not affected participants regarding BMD measurements and levels of vitamin D was tested in separate analyses, adjusted for sex, age, height and weight. This was done with SPSS in a logistic regression model. Results: No statistical difference was found between MIH affected and not affected participants when regards to vitamin D levels and BMD, but both values were lower in MIH affected girls. Boys severely affected by MIH, had on average significantly lower BMD values at the femoral neck compared to boys without MIH (P < 0.05). The prevalence of MIH was higher among participants with low serum levels of vitamin D compared to the participants with sufficient levels, but without reaching statistical significance. Conclusion: Severely MIH affected boys has lower BMD values in the femoral neck, compared to boys without MIH. It seems to be interesting to investigate severely MIH affected individuals in future studies. Keywords: Molar - Incisor Hypomineralization, Bone Mineral Density and 25 - hydroxyvitamin D